Definition of Software Reliability, Taking Into Account the Possibility of New Errors When Repairing Previously Detected - Ilmir Mubinovich Azymshin; Vsevolod Ozirisovich Chukanov (Безопасность информационных технологий, 2015)
In today's world to determine the reliability of software are widely used Jelinski-Moranda and Schick-Wolverton reliability models. But these models do not take into account the possibility that the developer can allow the appearance of new errors in correction of previously detected errors. The article discusses the option of modification of these models, taking into account the probability of emergence of error in correcting previously detected, that did not be before finalize the software. The article also contains studies of the probability of new errors when removing previously detected.